2002
DOI: 10.1017/s026502150200042x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of bupivacaine 0.2% and ropivacaine 0.2% combined with fentanyl for epidural analgesia during labour

Abstract: The results suggest that epidural bupivacaine 0.2% and ropivacaine 0.2% combined with fentanyl produced equivalent analgesia for pain relief during labour and delivery. It is concluded that ropivacaine 0.2% combined with fentanyl 2 microg mL(-1) provided effective analgesia with significantly less motor block and need for an instrumental delivery than a bupivacaine/fentanyl combination at the same concentrations during labour and delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 23 publications
1
17
0
Order By: Relevance
“…These cocktails have been shown to be effective in the acute perioperative period but have finite periods of action. Traditional amide local anesthetics such as bupivacaine or ropivacaine (which is reported to have a faster onset than bupivacaine but with a similar duration of action [2,7,11,12,22,25,37,41,50,52,55,58,74,86]) have been the mainstay of most TKA PAI cocktails. In addition to amide local anesthetics, some investigators have chosen to also include intrathecal morphine as part of their pain management protocol.…”
Section: Introductionmentioning
confidence: 99%
“…These cocktails have been shown to be effective in the acute perioperative period but have finite periods of action. Traditional amide local anesthetics such as bupivacaine or ropivacaine (which is reported to have a faster onset than bupivacaine but with a similar duration of action [2,7,11,12,22,25,37,41,50,52,55,58,74,86]) have been the mainstay of most TKA PAI cocktails. In addition to amide local anesthetics, some investigators have chosen to also include intrathecal morphine as part of their pain management protocol.…”
Section: Introductionmentioning
confidence: 99%
“…7 Asik et al concluded that epidural bupivacaine 0.2% and ropivacaine 0.2% combined with fentanyl produced equivalent analgesia for pain relief during labor and delivery. 8 It is concluded that ropivacaine 0.2% combined with fentanyl 2 microg mL (-1) provided effective analgesia with significantly less motor block and need for an instrumental delivery than a bupivacaine/fentanyl combination at the same concentrations during labor and delivery.…”
Section: Discussionmentioning
confidence: 96%
“…Yet again, the two local anaesthetics have not been compared in equipotent doses. In Aşlk and colleagues' study [7], the doses compared are high by today's standards and no effects of the addition of fentanyl have been observed due to this relatively high dose used. Also in Pirbudak and colleagues [16], no significant differences were observed between the two drugs, even if they were used at a lower concentration, but fentanyl was added in a dose effective on its own and may have masked the differences in analgesia due to the local anaesthetic solutions.…”
mentioning
confidence: 93%
“…In this issue of the European Journal of Anaesthesiology, Aşlk and colleagues compare the effects of epidurally administered fentanyl combined with either bupivacaine 0.2% or ropivacaine 0.2% for the initiation and maintenance of analgesia during labour and delivery [7]. Their results suggest that epidural block using bupivacaine 0.2% or ropivacaine 0.2%, combined with fentanyl, produces equivalent analgesia for pain relief during labour and delivery.…”
mentioning
confidence: 99%